Congenital muscular torticollis: experience of 14 cases - Das, BK; Matin, A; Hassan, GZ; Hossain, MZ; Zaman, MA (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Oct;19(4):555-60 The abstract of this article is available on the PubMed website